(untitled) (Journal of the College of Basic Education, 2022)
The research included five chaptersThe first chapter: the introduction and the importance of the research in that the functional variables as an influencing factor to achieve the integration of the overall physical fitness, as the weakness of this variable leads to a poor level of performance and then the inability to keep up with the requirements of the match.